Grey cast iron pulley / Shamsuri Mohd Daud, Mohd Najib Mamat and Mohd Noor Shahal Abdullah - Mohd Daud, Shamsuri; Mamat, Mohd Najib; Abdullah, Mohd Noor Shahal (Faculty of Mechanical Engineering, 1998)
Nowday,casting is a very important process in manufacturing production.Casting is made from metal which is melted, poured into mould,cooled,and solidified,shakeout,finishing and cleaning.To make casting the processes of melting metal^moulding,pouring,shakeout,and cleaning must be carried out. Various are used to melted metal.Casting are used because they are many advantages. Some of the advantages of casting were : -the complex shape product that can’t be made from another process like machining,forging and welding can be made by casting. -there are 110 wasted material than machining process. -it was a cheepers process than others. -it was suitable for mass product,e.g.for automotive industry. -steel scrap can be reused. Our project consist of Product Developement Of Gray Cast Iron Pulley(wood lathe machine).For our casting process,we used sand casting.The sample of the pulley are taken from wood lathe machine.The material for our product is grey cast iron(grade;FC 250).